Neethling Strain-Based Homologous Live Attenuated LSDV Vaccines Provide Protection Against Infection with a Clade 2.5 Recombinant LSDV Strain - Wannes Philips; Andy Haegeman; Nina Krešić; Laurent Mostin; Nick De Regge (Vaccines)
Background: Vaccination is the main control measure to prevent Lumpy skin disease (LSD), and Neethling-based homologous vaccines have been shown to be safe and effective against infection with classical clade 1.2 strains. In 2017, recombinant clade 2 LSDV strains originating from a badly produced and insufficiently controlled vaccine were first detected in Russia. A clade 2.5 recombinant strain spread from Russia throughout Southeast Asia and caused a massive epidemic. In this study, the efficacy of three different Neethling strain-based vaccines against the recombinant clade 2.5 LSDV strain was evaluated. Methods: For each vaccine, seven bulls were vaccinated and followed for three weeks to evaluate vaccine safety. Thereafter, vaccinated animals and non-vaccinated controls were challenged with a virulent clade 2.5 strain and followed for three more weeks to evaluate vaccine efficacy. Results: Only limited adverse effects were observed after vaccination, and all vaccinated animals seroconverted and showed an LSDV-specific cellular immune response after vaccination. After the challenge, the vaccinated animals developed almost no clinical signs, and no viremia or nasal excretion was detected. This was in sharp contrast with the non-vaccinated controls, where 8 out of 13 animals developed clinical disease with clear nodules. Most of these animals also had a prolonged period of fever, a clear viremia and excreted virus. Conclusions: Neethling-based LSDV vaccines can thus be considered safe and are effective not only against clade 1.2 LSDV strains, as was proven earlier, but also against a clade 2.5 recombinant strain.